Strategies for Improving Teacher Performance through Discipline among Elementary School Teachers - Sjafty Nursitii NP Maili; Sri Setyaningsih; Herfina Herfina (Newinera Publisher, 2026)
This study aims to identify strategies for improving elementary school teacher performance through discipline. Discipline is an important factor in creating a conducive learning environment and ensuring optimal achievement of educational goals. This research employs a quantitative approach using survey method and path analysis techniques. The population consisted of 516 elementary school teachers in Region 2 of East Jakarta, with a sample of 225 teachers selected through purposive sampling. Data were collected through questionnaires and analyzed using path analysis. The results show a direct and significant influence of discipline on teacher performance with a path coefficient value of y1 = 0.424, p < 0.05. This indicates that teachers with high discipline levels tend to demonstrate better performance in lesson planning, lesson implementation, evaluation of student learning outcomes, and additional tasks. The findings emphasize the need to increase awareness and improve discipline in the school environment to optimize basic education quality. Strategies for improving teacher performance include strengthening weak discipline indicators, namely time management (3.52) and compliance in following rules (3.66), while maintaining strong indicators such as rule enforcement (4.21) and responsibility (4.1). This study concludes that strong discipline can significantly improve teacher performance, and the stronger the discipline applied, the better the teacher performance outcomes.